Gating Properties of Mutant Sodium Channels and Responses to Sodium Current Inhibitors Predict Mexiletine-Sensitive Mutations of Long QT Syndrome 3 - Li, Gang; Woltz, Ryan L.; Wang, Cheng-yu; Ren, Lu; He, Pei-xin; Yu, Shan-dong; Liu, Xue-qin; Yarov-Yarovoy, Vladimir; Hu, Dan; Chiamvimonvat, Nipavan; Wu, Lin (Frontiers in Pharmacology, 2020)
Background: Long QT syndrome 3 (LQT3) is caused by SCN5A mutations. Late sodium current (late INa) inhibitors are current-specific to treat patients with LQT3, but the mechanisms underlying mexiletine (MEX)-sensitive (N1325S and R1623Q) and insensitive (M1652R) mutations remains to be elucidated. Methods: LQT3 patients with causative mutations were treated with oral MEX following i.v. lidocaine. Whole-cell patch-clamp techniques and molecular remodeling were used to determine the mechanisms underlying the sensitivity to MEX. Results: Intravenous administration of lidocaine followed by MEX orally in LQT patients with N1325S and R1623Q sodium channel mutation shortened QTc interval, abolished arrhythmias and completely normalized the ECG. In HEK293 cells, the steady-state inactivation curves of the M1652R channels were rightward shifted by 5.6 mV relative to the WT channel. In contrast, the R1623Q mutation caused a leftward shift of the steady-state inactivation curve by 15.2 mV compared with WT channel, and N1325S mutation did not affect steady-state inactivation (n = 5-13, P < 0.05). The extent of the window current was expanded in all three mutant channels compared with WT. All three mutations increased late INa with the greatest amplitude in the M1652R channel (n=9-15, P<0.05). MEX caused a hyperpolarizing shift of the steady-state inactivation and delayed the recovery of all three mutant channels. Furthermore, it suppressed late INa in N1325S and R1623Q to a greater extent compared to that of M1652R mutant channel. Mutations altered the sensitivity of Nav1.5 to MEX through allosteric mechanisms, by changing the conformation of Nav1.5 to become more or less favorable for MEX binding. Late INa inhibitors suppressed late INa in N1325S and R1623Q to a greater extent than that in the M1652R mutation (n =4-7，P < 0.05). Conclusion: The N1325S, R1623Q and M1652R mutations is associated with a variable augmentation of late INa, which was reversed by MEX. M1652R mutation changes the conformation of Nav1.5 that disrupt the inactivation of channel affecting MEX binding, corresponding to the poor response to MEX. The lidocaine test, molecular modeling and drugs screening in cells expressing mutant channels are useful for predicting the effectiveness of late INa inhibitors.